Pityriasis Rubra Pilar and hypothyroidism - Aline Martinez Franzotti; Juliana Centofanti Dentello Avelar; Thaís Abrão Cardoso; Mario Cesar Pires; Maria do Rosário Vidigal (Sociedade Brasileira de Dermatologia, 2014)
Pityriasis Rubra Pilaris (PRP) is a chronic and rare papulosquamous disorder. Treatment of Pityriasis Rubra Pilaris is based on empiric evidence because of several doubts regarding its etiology and also because of its relative rarity, making randomized studies difficult to perform. Some factors suggest that the metabolism of vitamin A is involved in pathogenesis. We report a case of Pityriasis Rubra Pilaris associated with autoimmune hypothyroidism which presented rapid and complete response after thyroid hormone replacement, without any association with other systemic treatment. In literature there are only three other reports of significant improvement of the lesions after hormonal correction. Deficiency of thyroid hormone inhibits the conversion of carotene into vitamin A, which would be responsible for the occurrence of Pityriasis Rubra Pilaris in this patient.